Investigating the anticancer and synergistic effects of the combination of green synthesized silver nanoparticles and papaverine on breast cancer cell lines: focusing on the apoptosis pathway and microRNA regulation - Maryam Fekri Soufiabadi; Reza Haji Hosseini; Zolfaghar Lotfi (Artificial Cells, Nanomedicine, and Biotechnology)
The study investigates the anticancer effects of green silver nanoparticles (Ag-NPs) synthesized from Viola cornuta extract combined with papaverine on breast cancer cells. Ag-NPs were characterized using various analytical techniques, confirming their presence with UV–vis spectroscopy showing a peak at 413 nm and an average size of 42 nm via field emission scanning electron microscopy (FE-SEM) analysis. The particles demonstrated a face-centred cubic structure, with energy-dispersive X-ray spectroscopy (EDX) confirming elemental composition. Additionally, the zeta potential measurement of −6.75 mV indicated favourable electrostatic repulsion between nanoparticles, thereby confirming their stability. Antioxidant activity was significant, with an EC50 value of 38.78 μg/mL. The combination treatment of Ag-NPs and papaverine exhibited synergistic effects, lowering IC50 values to 2.8 + 112.7 μg/mL for MCF-7 cells and 6.2 + 112 μg/mL for MDA-MB-231 cells, without toxicity to normal cells. Flow cytometry revealed G0/G1 phase inhibition and increased sub-G1 populations, indicating cell cycle arrest, alongside increased reactive oxygen species generation and apoptosis. Notably, the experimental group showed altered expression of oncogenic and tumour suppressor microRNAs and apoptotic genes (p < .0001), underscoring the potential of this nanoparticle-papaverine combination as an effective anticancer strategy against breast cancer treatment resistance.